Seed Germination and DNA genotyping of Neolamarckia cadamba (Roxb.) Progenies (half-sib family) - Nurfaizah, Bt Matra; Petrus, Bulan; Ho Wei, Seng (2011)
Neolamarckia cadamba or locally known as Kelampayan is an economically and ecologically important forest tree species. The species is an indigenous fast growing tree that gives early economic returns, within eight to ten years. Kelampayan has been planted in plantation for commercial purposes due to its wood characteristics that are suitable to produce different products, such as plywood and paper. In the present study, germination test was used to determine the seed viability and to gain more information with respect to field planting value of the Kelampayan seeds. Germination test also can provide results which can be used to compare the value of different seed lots. Fruits of ten mother trees from the Ravens Court, Lawas, Sarawak, were processed and air-dried to collect the seeds. The germination test was conducted on the filter paper under optimum condition and the growth rates between progenies of different mother trees were compared. Progenies from mother tree number 00059, showed the highest germination rate (88%) while progenies from mother tree number 00067 showed the lowest germination rate (14%). The information on germination test can be used to predict the rate of germinating progenies from different mother trees and to determine the planting value of seed lots to provide standardized marketing seed. For DNA genotyping, a total of 139 progenies from the 7 selected mother trees earlier were genotyped using four SSR primers, namely AC03, AC11, AC15 and GTG11. All 4 loci were successfully amplified and a total of 17 alleles were detected. The value for He was highest for NCAC11 (0.7190) and lowest for NCGTG11 (0.3832).